2015
DOI: 10.1093/hmg/ddv499
|View full text |Cite
|
Sign up to set email alerts
|

De novodominantASXL3mutations alter H2A deubiquitination and transcription in Bainbridge–Ropers syndrome

Abstract: De novo truncating mutations in Additional sex combs-like 3 (ASXL3) have been identified in individuals with Bainbridge-Ropers syndrome (BRS), characterized by failure to thrive, global developmental delay, feeding problems, hypotonia, dysmorphic features, profound speech delays and intellectual disability. We identified three novel de novo heterozygous truncating variants distributed across ASXL3, outside the original cluster of ASXL3 mutations previously described for BRS. Primary skin fibroblasts establishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
110
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(116 citation statements)
references
References 74 publications
(82 reference statements)
4
110
0
2
Order By: Relevance
“…9 Until recently, only nine different de novo truncating ASXL3 germline variants have been identified in individuals with the clinical diagnosis of BRPS. 2,[10][11][12] Thus, available information about BRPS is still limited. In addition, three different LoF variants have been identified in a large autism cohort.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9 Until recently, only nine different de novo truncating ASXL3 germline variants have been identified in individuals with the clinical diagnosis of BRPS. 2,[10][11][12] Thus, available information about BRPS is still limited. In addition, three different LoF variants have been identified in a large autism cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Patient 1 by Srivastava et al 11 patient 1 was not able to sit, crawl or stand at age 6 years, patient 2 was not able to walk at age 4 years and patient 3 was unable to roll over or sit upright at age 13 months. 11 The patient published by Hori et al 12 was able to sit without support at age 2 years and to stand holding on to things at age 3 years. Speech development was also impaired in all 12 patients in whom this information was available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Srivastava et al 9 showed that additional sex combs like 3 (ASXL3) interacts with BAP1, a hydrolase that removes mono-ubiquitin from histone H2A lysine 119 (H2AK119Ub1) as a component of the polycomb repressive deubiquitination (PR-DUB) complex. The authors observed a significant increase in H2AK119Ub1 in ASXL3 patient fibroblasts, highlighting an important functional role for ASXL3 in PR-DUB mediated deubiquitination.…”
Section: Introductionmentioning
confidence: 99%
“…El fenotipo sutil y variable deriva en que el diagnóstico se establece con la secuenciación completa del genoma o del exoma 3,[8][9][10][11] . Las características clíni-cas comunes, retraso psicomotor grave, dismorfias faciales, falla del crecimiento y dificultades para la alimentación se confunden con otros síndromes como el síndrome de Bohring-Opitz (BOS, MIM # 605039) (tabla 1) 12,13 .…”
unclassified